Mixed metal sulfides for electrochemical energy storage and conversion - Yu, Xin Yao (2020)
Mixed metal sulfides (MMSs) have attracted increased attention as promising electrode materials for electrochemical energy storage and conversion systems including lithium-ion batteries (LIBs), sodium-ion batteries (SIBs), hybrid supercapacitors (HSCs), metal–air batteries (MABs), and water splitting. Compared with monometal sulfides, MMSs exhibit greatly enhanced electrochemical performance, which is largely originated from their higher electronic conductivity and richer redox reactions. In this review, recent progresses in the rational design and synthesis of diverse MMS-based micro/nanostructures with controlled morphologies, sizes, and compositions for LIBs, SIBs, HSCs, MABs, and water splitting are summarized. In particular, nanostructuring, synthesis of nanocomposites with carbonaceous materials and fabrication of 3D MMS-based electrodes are demonstrated to be three effective approaches for improving the electrochemical performance of MMS-based electrode materials. Furthermore, some potential challenges as well as prospects are discussed to further advance the development of MMS-based electrode materials for next-generation electrochemical energy storage and conversion systems.